2020
DOI: 10.1002/kin.21400
|View full text |Cite
|
Sign up to set email alerts
|

Detailed experimental and kinetic modeling study of 3‐carene pyrolysis

Abstract: 3-Carene is an important potential biofuel with properties similar to the jetpropellant JP-10. Its thermal decomposition and combustion behavior is to date unknown, which is essential to assess its quality as a fuel. A combined experimental and kinetic modeling study has been conducted to understand the initial decomposition of 3-carene. The pyrolysis of 3-carene was investigated in a jet-stirred quartz reactor at atmospheric pressure, at temperatures varying from 650 to 1050 K, covering the complete conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…KinBot has been used by Zhang et al 64 to study the hightemperature unimolecular decomposition pathways of 3-carene and to understand the initial steps of its pyrolysis. Beyond the expected unimolecular pathways, KinBot suggested a direct molecular hydrogen-elimination reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KinBot has been used by Zhang et al 64 to study the hightemperature unimolecular decomposition pathways of 3-carene and to understand the initial steps of its pyrolysis. Beyond the expected unimolecular pathways, KinBot suggested a direct molecular hydrogen-elimination reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…KinBot , is a workflow code that drives a series of quantum-chemical calculations with the aim to go from structure to rate coefficients. It has been applied to a wide range of gas-phase chemical kinetics problems by us , and others. KinBot targets reactions of organic species in the gas phase. A detailed description of the code is provided in ref ; therefore, here we present a relatively brief overview.…”
Section: Methodsmentioning
confidence: 99%
“…Arunan and co-workers , observed that the product distribution from the supercritical pyrolysis of 3-carene (8–14 bar, 650–950 °C) is primarily composed of light linear hydrocarbons such as acetylene, allene, and butadiene, along with minor products like toluene, benzene, and cyclopentadiene. In contrast, Zhang et al reported that the major products obtained from 3-carene pyrolysis were primarily cyclic compounds in the temperature range of 480–675 °C, with the abundance of cymene at low temperatures. Toluene dominated the products in a wide temperature range (540–780 °C), while xylene’s and benzene’s productions increased with temperature.…”
Section: Introductionmentioning
confidence: 92%
“…In spite of its potential fuel properties, 3-carene has received low research interest as a potential jet fuel. Sharath et al and Zhang et al are among the researchers who explored 3-carene as a prospective fuel. Arunan and co-workers , observed that the product distribution from the supercritical pyrolysis of 3-carene (8–14 bar, 650–950 °C) is primarily composed of light linear hydrocarbons such as acetylene, allene, and butadiene, along with minor products like toluene, benzene, and cyclopentadiene.…”
Section: Introductionmentioning
confidence: 99%